THE EFFECT OF PRODUCT QUALITY AND PRICE OF ACCESSORIES ON PURCHASING DECISIONS FOR TOKOPEDIA APPLICATION CUSTOMERS - Syahpul Nove Putra Telaumbanua; Slamet Sutrisno (OIKONOMIA: Journal of Economics and Management Science, 2024)
In the era of industrial revolution 4.0, the development of communication technology is increasing so that people can enjoy ease in communicating. For entrepreneurs to create marketing strategies to expand the market by creating or providing online stores. Purchasing decisions have a very important role because they can increase profits for the company in improving the products being marketed. The aim of this research is to find out and analyze how much influence product quality and accessory prices have on Tokopedia users' purchasing decisions. The sample used was STIE UNISADHUGUNA students majoring in economics and totaling 69 students. The results obtained show that product quality does not have a positive and significant effect on purchasing decisions, and price has a positive and significant effect on purchasing decisions